Transcriptional responses of Medicago truncatula upon sulfur deficiency stress and arbuscular mycorrhizal symbiosis - Wipf, Daniel; Mongelard, Gaëlle; van Tuinen, Diederik; Gutierrez, Laurent; Casieri, Leonardo (Frontiers in Plant Science, 2014)
Sulfur plays an essential role in plants’ growth and development and in their response to various abiotic and biotic stresses despite its leachability and its very low abundance in the only form that plant roots can uptake (sulfate). It is part of amino acids, glutathione (GSH), thiols of proteins and peptides, membrane sulfolipids, cell walls and secondary products, so reduced availability can drastically alter plant growth and development. The nutritional benefits of symbiotic interactions can help the plant in case of S deficiency. In particular the arbuscular mycorrhizal (AM) interaction improves N, P and S plant nutrition, but the mechanisms behind these exchanges are not fully known yet. Although the transcriptional changes in the leguminous model plant Medicago truncatula have been already assessed in several biotic and/or abiotic conditions, S deficiency has not been considered so far. The aim of this work is to get a first overview on S-deficiency responses in the leaf and root tissues of plants interacting with the AM fungus Rhizophagus irregularis. Several hundred genes displayed significantly different transcript accumulation levels. Annotation and GO ID association were used to identify biological processes and molecular functions affected by sulfur starvation. Beside the beneficial effects of AM interaction, plants were greatly affected by the nutritional status, showing various differences in their transcriptomic footprints. Several pathways in which S plays an important role appeared to be differentially affected according to mycorrhizal status, with a generally reduced responsiveness to S deficiency in mycorrhized plants.